PHENOL - WHEAT PROTEIN - FORMALDEHYDE ADHESIVES FOR WOOD - BASED PANELS - Marie-Christine LAGEL; Antonio PIZZI; Andreas REDL (Pro Ligno, 2014)
Phenol-formaldehyde (PF) resins were prepared with a level of 10%, 20% and 30% substitution of the phenol in the resin by three types of wheat gluten protein hydrolysates having different characteristics, namely (i) an enzymatic hydrolysate, (ii) a lower molecular weight enzymatic hydrolysate, and (iii) a middle sized molecular weight acid hydrolysate. The mixed protein-phenolic oligomer species distribution formed in the preparation of these resins were identified by matrix assisted laser desorption ionization time of flight (MALDI-TOF) mass spectrometry.